Empowerment Model of Migrant Workers - Tika Widiastuti; Muhammad Nafik Hadi Ryandono; Imron Mawardi (Perisai : Islamic Banking and Finance Journal, 2017)
The profession of migrant workers in some cases bring the person concerned to get the treasures expected success, but not rarely contain a number of risks that need to get the attention of government authorities. A number of problems that might be experienced when Indonesian Labor not available works. Therefore it takes a model economic empowerment for the labor of Indonesia, when he returned to his country was able to survive and improve the well-being of himself and of his family. This research aims to know the role of zakah's institution towards the empowerment of Indonesia's labor and to devise appropriate empowerment model for Indonesian Workforce by Institution of Zakah. Data analysis was done with a qualitative approach. Analytical techniques in the study will be conducted with qualitative analysis approach, a case study of eksplanation to explain how the empowerment model right for Indonesia in Labor Studies. Based on the data and the results of the analysis that has been done can be known that Dompet Dhuafa has role in Indonesia Workforce empowerment. The empowerment Model implemented by Dompet Dhuafa form the Groove program that may help the former workforce of Indonesia after plunging back to life in his native region. Former Indonesian workforce empowerment meant to monitor and nurture the entrepreneurial activities are continuously carried out by former Indonesian labor so that it can be a permanent effort.